Tanglefoot Difusor New Method Insect Destroyer - Science History Institute (2018)
The Tanglefoot Company first introduced the Difusor insecticide sprayer and Difuso insecticide in 1932. Difuso was a pyrethrum-based insecticide. At the time, the Difusor was considered a revolutionary new method of insect control because it used electrically generated steam vaporization to expel the insecticide. The insecticide and steam were intermixed in the nozzle to emerge as an extremely fine vapor floated in the air and filled the cracks and crevices of the room with insecticide. The theory of the device was very simple, using the age old perfume atomizing principle. It was invented to replace flypaper, the flyswatter and the hand sprayer. This unit incorporated a brown glass bottle attached to a metal stand with a black handle. The metal stand had a glass jar inside with an immersion heating element. The internal glass jar was filled with water and the brown glass bottle with insecticide. The unit was plugged into an outlet to heat the water and then generate steam to vaporize the insecticide into the room and had an automatic shut-off when the water evaporated. There is a cut out arrow shape design on the metal stand that allows view of the water line.
Keywords: Pests--Control; Pesticides; DDT (Insecticide); Tanglefoot Company; Insecticides